Evaluation of a Biostimulant (Pepton) Based in Enzymatic Hydrolyzed Animal Protein in Comparison to Seaweed Extracts on Root Development, Vegetative Growth, Flowering, and Yield of Gold Cherry Tomatoes Grown under Low Stress Ambient Field Conditions - Polo, Javier; Mata, Pedro (Frontiers in Plant Science, 2018)
The objectives of this experiment were to determine the effects of different application rates of an enzyme hydrolyzed animal protein biostimulant (Pepton) compared to a standard application rate of a biostimulant derived from seaweed extract (Acadian) on plant growth parameters and yield of gold cherry tomatoes (Solanum lycopersicum L.). Biostimulant treatments were applied starting at 15 days after transplant and every 2 weeks thereafter for a total of 5 applications. One treatment group received no biostimulant (Control). Three treatment groups (Pepton-2, Pepton-3, Pepton-4) received Pepton at different application rates equivalent to 2, 3, or 4 kg/ha applied by foliar (first 2 applications) and by irrigation (last 3 applications). Another treatment group (Acadian) received Acadian at 1.5 L/ha by irrigation for all five applications. All groups received the regular fertilizer application for this crop at transplantation, flowering, and fruiting periods. There were four plots per treatment group. Each plot had a surface area of 21 m2 that consisted of two rows that were 7 m long and 1.5 m wide. Plant height, stem diameter, distance from head to bouquet flowering, fruit set distance between the entire cluster and cluster flowering fruit set, leaf length, and number of leaves per plant was recorded for 20 plants (5 plants per plot) at 56 and 61 days after the first application. Root length and diameter of cherry tomatoes were determined at harvest from 20 randomly selected plants. Harvesting yield per plot was registered and production per hectare was calculated. Both biostimulants improved (P < 0.05) all vegetative parameters compared with the control group. There was a positive linear (P < 0.001) effect of Pepton application rate for all parameters. The calculated yield was 7.8 and 1 Ton/ha greater that represent 27 and 2.9% higher production for Pepton applied at 4 kg/ha compared to the control and to Acadian, respectively. In conclusion, Pepton was effective improving yield of gold cherry tomatoes under the low stress ambient growing conditions of this experiment. Probably short-chain peptides present in Pepton are involved in endogenous hormones and metabolic mediators that could explain the results obtained in this study.